Analytical model of interaction of tide and river flow - Phairot Chatanantavet; Suphat Vongvisessomjai (Songklanakarin Journal of Science and Technology (SJST), 2006)
Hydrodynamic characteristics of a river resulting from interaction of tide and river flow are important since problems regarding flood, salinity intrusion, water quality and sedimentation are ubiquitous. The lower reach of the river strongly influenced by tides from the sea, when interacting with river flows, results in a complicated pattern which is simplified to its interaction with four main constituents of tides obtained from harmonic analysis. An analytical model is developed in this study for simulating the hydrodynamic processes in estuarine waters, with the emphasis being given to the interaction between tides and river flows. The perturbation method is used to derive the analytical solution, in which the estuarine flow is separated into steady and unsteady components. Thus the analytical solutions derived consist of two distinct parts; one represents the influence of river flows and the other represents the influence of tides. The application of the model to a case study, the Chao Phraya river, which requires a time series of discharges and loadings at the river mouth to model water quality in the Gulf of Thailand, shows that the model can beautifully and completely simulate the hydrodynamic features of tide and river flow interaction especially in the rainy season when the river discharge is high. Data of tidal discharges are scarce because of high cost of measurement especially in the lower reach of the river strongly influenced by tides from the sea. From this study of relation between tidal discharges and tides, the analytical model can compute tidal discharges from tides correctly. The results of tides and tidal flow can subsequently be used to calculate eddy viscosity and dispersion coefficient for describing salinity and water quality profiles.